Protein phosphatase activities in the serum and saliva of healthy children - Chaves Neto, Antonio Hernandes [UNESP]; Sassaki, Kikue Takebayashi [UNESP]; Nakamune, Ana Cláudia de Melo Stevanato [UNESP] (My University, 2011)
The purpose of this study was to investigate the activities of the total acid phosphatase (TAP), tartrate-resistant acid phosphatase (TRAP), low molecular weight protein tyrosine phosphatase (LMW-PTP) and alkaline phosphatase (ALP) enzymes, as well as the possible correlation in the serum and in unstimulated whole saliva of children. Enzymatic activities were measured in pairs of concurrently obtained serum and salivary samples from 32 children in good oral and systemic health (16 of each sex) with a median age of 6.4 ± 3.3 years (range 1.08 – 12.92 years). All collections were made between the hours of 08:00 – 10:00 a.m. We used p-nitrophenyl phosphate as the substrate in the enzymatic assay for TAP, TRAP and LMW-PTP, and thymolphthalein monophosphate as the substrate for ALP. The enzymatic activities of all the studied enzymes were higher in serum than in saliva. The mean of enzymatic activities of serum TAP, TRAP, LMW-PTP and ALP were 36.51 ± 8.21, 23.99 ± 5.73, 11.16 ± 5.65 and 76.50 ± 17.32 U/L, respectively, while the mean salivary TAP, TRAP, LMW-PTP and ALP enzymatic activities were 9.60 ± 5.04, 1.36 ± 0.87, 5.65 ± 3.07 and 4.08 ± 1.83 U/L in this order. The TRAP revealed a positive linear correlation between its activity in the serum and saliva (Spearman r = 0,4685, p < 0,05). We concluded that the salivary TRAP has a potential to be use as biomarkers of pathologies and states that modify its activity in the serum.

O objetivo deste estudo foi investigar as atividades das enzimas fosfatase ácida total (FAT), fosfatase ácida resistente ao tartarato (TRAP), proteína tirosina fosfatase de baixa massa molar (LMW-PTP) e fosfatase alcalina (FAL), como também a possível correlação no soro e na saliva total não estimulada de crianças. As atividades enzimáticas foram mensuradas simultaneamente no soro e na saliva de 32 crianças (16 de cada sexo) com boa saúde oral e sistêmica, com média de idade de 6,4 ± 3,3 anos (variando entre 1,08 – 12,92 anos). Todas as coletas foram realizadas entre 8 e 10 h da manhã. Foi utilizado como substrato p-nitrofenil fosfato para a análise de FAT, TRAP e LMW-PTP, e timolftaleína monofosfato para análise de FAL. As atividades enzimáticas de todas as enzimas estudadas foram maiores no soro que na saliva. As médias ± dp das atividades enzimáticas para FAT, TRAP, LMW-PTP e FAL no soro foram 36,51 ± 8,21, 23,99 ± 5,73, 11,16 ± 5,65 e 76,50 ± 17,32 U/L, respectivamente, enquanto para a saliva foram, na mesma sequência, 9,60 ± 5,04, 1,36 ± 0,87, 5,65 ± 3,07 e 4,08 ± 1,83 U/L. A TRAP mostrou uma correlação linear positiva entre sua atividade no soro e na saliva (Spearman r = 0,4685, p < 0,05). Conclui-se que a TRAP salivar possui potencial para ser utilizada como biomarcador de patologias e estados que alterem sua atividade no soro.
Atividade de proteínas fosfatases no soro e saliva de crianças saudáveis
Keywords: Fosfatase ácida; Fosfatase alcalina; Saliva; Soro; Acid phosphatase; Alkaline phosphatase; Saliva; Serum